ENCOURAGE STUDENTS TO THINK CRITICAL AND INNOVATIVE WITH THE PROBLEM BASED LEARNING MODEL - Nasya Putri Nabila; Fandra Apriyandi Rahayu; elfina, Elfina Mei Rahmawati (CV. Fahr Publishing, 2024)
Critical and innovative thinking are essential skills for students to develop in order to make appropriate decisions and solve problems with creative and effective solutions. This study aims to explore how the Problem Based Learning (PBL) model can encourage students to think critically and innovatively. The research method used is qualitative with a case study design applied within the PBL framework. The results show that the teacher's role is highly significant in shaping students' critical and innovative thinking skills through this learning model. Some strategies that teachers can use to encourage critical and innovative thinking include creating and facilitating interactions among students during the learning process, training students to produce work, and developing their thinking processes